Sepsis: Antibiotic Resistances of Gram-Positive and Gram-Negative Bacterial in a Tertiary Care Hospital - Siti Nurul Jannah; Muhammad Vitanata Arfijanto; Musofa Rusli; Agung Dwi Wahyu Widodo (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Sepsis is a systemic infection that causes multiorgan failure and death. The death rate that is caused by sepsis is increasing. This high value of death has a correlation with the resistance of antibiotics. However, increased antibiotic resistance is not balanced with new research about antibiotics. As a consequence, it causes difficulties in handling sepsis patients who need antibiotic 1-2 hours after diagnosis is enforced. Methods: This was a descriptive study with case study design to analyze medical records of the patients, evaluating the pattern of bacterial resistance to antibiotic in 221 patients with sepsis with 240 blood isolates to identify. Results: From 221 patients identified as sepsis, there were 97 male patients (43.9%) and 124 female patients (56.1%), mostly between 18-59 years old (63.8%), with the highest level in female (54.8 %) and elderly (66.3%). The bacteria that caused the most sepsis were gram-positive. The most species in gram-positive are Staphylococcus haemolyticus (16.3%) and Staphylococcus aureus (12.5%), and the most species in gram-negative is Escheriichia coli (13.3%). The most sensitive antibiotics in gram-positive bacteria were Piperacillin-Tazobactam (100%), Daptomycin (99.2%), and Clindamycin (99.2%). The sensitive antibiotics in gram-negative bacteria were Amikacin (85.9%), Cefoperazone (84.6%), and Piperacillin-Tazobactam (84.1%). Conclusion: The most sensitive antibiotics in gram-positive bacteria were Piperacillin-Tazobactam, Daptomycin, and Clindamycin. The sensitive antibitics in gram-negative bacteria were Amikacin, Cefoperazone, and Piperacillin-Tazobactam.